Electrical characterization of ZnO-coated nanospring ensemble by impedance spectroscopy: probing the effect of thermal annealing. (25th March 2019) - Bastatas, Lyndon D; Wagle, Phadindra; Echeverria, Elena; Slinker, Jason D; McIlroy, David N
Abstract: The effects of thermal annealing on the electrical properties of randomly oriented ZnO-coated nanospring ensembles were extensively investigated through AC impedance spectroscopy. Annealing the nanospring mats for an hour at 873 K in air showed significant change in ZnO morphology, reduced electrical conductivity due to the presence of grain boundaries, decreased apparent donor concentration, and faster decay of sub-band gap photocurrent. The role of the nanospring-nanospring junctions in the conduction of carriers in the ensemble was also examined, as well as evaluation of their responsiveness to thermal and optical stimulations. This work identifies the effects of heat treatment in the presence of air on the electrical properties of the nanospring ensembles, which are related to the mesoscopic morphology and interconnect within the ensemble and the properties of the ZnO coating.